PREPARING STUDENTS FOR SOCIAL ACTIVITIES BASED ON A DIFFERENTIAL APPROACH (American Journal of Pedagogical and Educational Research, 2024)
This article presents information on preparing students for social pedagogical activities based on a differential approach and highlights the opportunities of differential education.